Two-center convergent close-coupling calculations for positron-lithium collisions - Lugovskoy, Andrey; Kadyrov, Alisher; Bray, Igor; Stelbovics, Andris (American Physical Society, 2010)
We report on two-center convergent close-coupling calculations of positron-lithium collisions. The target is treated as one active electron interacting with an inert ion core. The positronium formation channels are taken into account explicitly utilizing both negative- and positive-energy Laguerre-based states. A large number of channels and high partial waves are used to ensure the convergence of the cross sections. We find the Ramsauer-Townsend minimum in total and elastic cross sections at an impact energy E of about 0.0016 eV. As found previously forH and He, the contributions to the breakup cross section from both the Li and the Ps centers become the same as the threshold is approached.